Digital Gamification: Application of Kahoot in Teaching ‎The Biology Subject - Mutiva , Sheilla Indiaka; Mwangi , Prof. Ronald Waweru; Wekesa , Dr. Jael Sanyanda (International Journal of Basic and Applied Sciences, 2025)
Digital technology has increasingly transformed the landscape of science education, positioning gamification as a powerful pedagogical tool ‎to enhance learner engagement and comprehension. This study investigates the application of digital gamification using ‘Kahoot!’ to enhance ‎comprehension of biology subject content among secondary school students. The study seeks to determine the effectiveness of digital ‎gamification in reinforcing students’ understanding of cell organelles; examine learners’ motivation during the gamified learning process; ‎and evaluate the impact of a digital gamification intervention through pre- and post-intervention assessments. A quasi-experimental design ‎was employed involving two groups: an experimental group using ‘Kahoot!’ -based digital quizzes and learning content, and a control ‎group exposed to traditional teaching methods. The study targeted Form Two biology students, with gamified content aligned to the cell ‎organelles topic in the Kenyan secondary school curriculum. Data was collected using comprehension tests. Quantitative analysis through t-test revealed statistically significant improvements in comprehension, motivation, and engagement levels among students in the experimental ‎group compared to the control group. The findings demonstrate that digital gamification fosters deeper understanding, enhances motivation, ‎and promotes active participation in biology lessons. The study recommends the integration of digital gamification tools like ‘Kahoot!’ into ‎science instruction to foster a more interactive and learner-centered environment‎.